Liposome-Chitosan Nanoparticle Complexes as An Effective System for Ocular Drug Delivery - Araf Mahefuzabibi Hidayat; Naveen Kumar B D; Arpan K Tripathi; Matsyagiri Lenkalapally; Bhupen Kumar Baruah; Pranit Saraswat; Rohini Armo; Pankaj Gupta; Meesala Sudhakar; Yogesh Matta (The Bioscan, 2024)
This study examined the possibility of liposome-chitosan nanoparticle complexes as an effective system for ocular drug delivery. The researchers tested varying ratios of chitosan-liposomes in their study, examining entrapment efficiency, cumulative drug release, and ocular tissue distribution. The findings were that increments in chitosan concentration can significantly enhance drug entrapment, slow-release profiles, and penetration into ocular tissues, especially the cornea, conjunctiva, and retina. Liposome–chitosan complexes showed an excellent drug retention and increased penetration through the tissues due to its mucoadhesive properties of chitosan. These results suggest that liposome–chitosan nanoparticle complexes have potential for sustained, localized, and more efficient ocular drug delivery overcoming the biological barriers in increasing bioavailability as a treatment of ocular diseases.